On Uncertain Lifetimes - Barro, Robert J.; Friedman, James W. (Journal of Political Economy, 1977)
This paper contrasts consumer choice under uncertain lifetimes with the behavior that would arise if each individual's lifetime were announced at birth. In a model that includes life insurance and excludes investments in human capital, the expected utility under uncertain lifetimes exceeds that under known lifetimes when the latter expectation is based on preannouncement survival probabilities. This conclusion emerges, first, because the model without human capital contains no planning benefits from knowledge of the horizon and, second, because the prior announcement of lifetimes forces risk-averse consumers to undertake an extra gamble that they could otherwise avoid by using life insurance.